Unobserved effects of monetary policy in the Peru’s departments output and unemployment - Mendoza Vargas, Oscar Manuel (2023)
This is the first article in a series of two. A NAIRU-Keynesian model is developed for Peru’s departments (regions) to analyse whether there is a stable relationship between inflation and unemployment, and inflation and the output gap as documented in the Peruvian literature. I applied GLS for model estimation. My results document a positive relationship between future inflation rates and the gap in departmental unemployment rates concerning national unemployment rates, I evidence the Phillips curve flattening at the departmental level when estimating with the output gap, which is consistent with the national aggregate models, but there is a more elastic relationship when estimating with departmental unemployment rates. This represents unobserved effects for the monetary policy maker and requires further research.